CERTAIN ISSUES CONCERNING CONTRACTS ON SUPPORT FOR LIFE AND CONTRACTS ON SUPPORT UNTIL DEATH (EU and comparative law issues and challenges series (ECLIC), 2019)
Contracts on support for life and contracts on support until death are two very similar contracts that are concluded between a provider of support and a recipient of support. Its purpose is to procure support to a person that needs it, until his/her death. The provider of support will, according to the contract that was concluded, receive his/her payment either right after the drafting of a contract or after the receiver of support dies. The payment will be comprised of a part or of whole of recipient’s property. The first part of this paper will deal with these contracts in general. Since contracts on support for life and support until death are somewhat controversial due to certain problems that are related to them, the second part of that paper will outline these issues. First, it will deal with the fact that the heirs of recipient of support will not inherit the property that will be received by the provider of support, since that property is not inheritable. Therefore, this contract is sometimes concluded with the sole purpose of bypassing forced heirs and transferring recipient’s property to those he/she wants to inherit it. For that reason, forced heirs will often try to annul these contracts, even if contractual parties did not try to bypass them unlawfully. The second problem is connected to the fact that senior citizens, usually due to their lack of legal knowledge, are not aware of all of the rights they have according to these contracts. Because of that, they will sometimes end up without the support they expected but also without the property that was meant to be a remuneration for that support. Even if some of them had the right to seek legal help, due to their advancing age, they might not have enough time to wait for a court to reach its decision. This paper will also explore whether these types of contracts exist in other countries in the EU and how are they different from contracts on support for life and support until death in Croatia.